Lessons learned-local residents’ acceptance of crowding during public - Jabil Mapjabil; Mohamad Pirdaus Yusoh; Muhamad Azahar Abas; Nurhazliyana Hanafi; MohdJirey Kumalah; Normah Abdul Latip (International Journal of Special Education (IJSE), 2022)
Pangkor Island is one of the islands that is the focus of tourists from within and outside the country—as evidenced by the very high number of tourist arrivals, especially on public holidays. The arrival of many tourists will have an impact on the locals as well as bring about various levels of acceptance. It can be difficult to achieve sustainable tourism development. Therefore, this study was conducted to examine the situation of crowding that occurs in Pangkor Island during public holidays and the level of acceptance of local residents to the situation. This quantitative study used a questionnaire to survey a total of 387 local residents. Using the People at One Time (PAOT) method, respondents were given five choices of pictures showing the tourism situation in Pangkor Island during public holidays. From this PAOT analysis, respondents stated that the situation in Pangkor Island on public holidays was 'very crowded' with 74.4% choosing Photo F, followed by Photo D (9.6%), Photo E (7.2%) and finally, the photo with lowest percentage was Photo A (1.3%). The average frequency of respondents seeing tourists carrying out selected activities in tourism is also high with a mean value of 4.15. The crowding situation in Pangkor Island during public holidays puts the barometer of the level of acceptance of the locals at a moderate level with a mean value of 2.87. This situation shows that the locals can still accept the number of tourist arrivals, but that there is already a conflict. If this condition continues without any improvement, it can cause the barometer reading to increase to the red level which is unacceptable. This study provides important information to stakeholders to ensure the sustainability of tourism in Pangkor Island is preserved.